Strength–Ductility Synergy of Lightweight High Entropy Alloys - Fainah Madewu; Nicholus Malatji; Mxolisi Brendon Shongwe; Tawanda Marazani; Lehlogonolo Rudolf Kanyane (Engineering Reports)
ABSTRACT Lightweight high entropy alloys (LWHEAs) are a unique class of materials that combine numerous principal elements such as Al, Mg, and Ti, in equiatomic or near‐equiatomic ratios. These alloys are suitable for high‐performance applications in the aerospace, automotive, and defense industries due to their exceptional balance of lightweight, high strength, and superior ductility. The biggest obstacle in the development of LWHEAs is to attain a strength–ductility synergy. The mechanical performance of these alloys is influenced by intricate interactions between solid‐solution strengthening, lattice distortion, and phase stability mechanisms, as well as intricate deformation processes like transformation‐induced plasticity (TRIP) and twinning‐induced plasticity (TWIP). There remains a critical knowledge gap regarding how process parameters and processing methods influence the mechanical properties and microstructure, which are key factors in determining the strength–ductility synergy of LWHEAs. This study evaluated and figured out that the balance between strength and ductility in LWHEAs can be enhanced by optimizing microstructure through customized alloying and heat treatments. Various strategies, including the introduction of coherent precipitates, hierarchical structures, and grain refinement have also demonstrated usefulness in enhancing mechanical performance. The article presented a detailed review of the recent progress in the attainment of strength–ductility synergy in LWHEAs.